Responsive feeding and child interest in food vary when rural Malawian children are fed lipid-based nutrient supplements or local complementary food - Flax, Valerie L.; Mäkinen, Samppa; Ashorn, Ulla; Cheung, Yin Bun; Maleta, Kenneth; Ashorn, Per; Bentley, Margaret E. (Maternal and child nutrition, 2013)
Caregiver and child behaviours during feeding have been used to measure responsiveness, which has been recognised as important for child growth and development. The aims of this study were to understand how caregiver and child behaviours differ when feeding lipid‐based nutrient supplements (LNS) vs. local complementary food and to detect associations between behaviours and child interest in food. Sixteen moderately underweight 6–17‐month‐old Malawian children receiving 50 g/day of supplementary LNS for 12 weeks were videotaped during LNS (n = 32) and local complementary feeding (n = 28) episodes. Behaviours were coded at the level of the intended bite (1674 total bites). The analysis used regression models adjusted for within‐subject correlation. Caregivers were less likely to allow children to self‐feed and more likely to use physical pressure during LNS vs. complementary food bites. Positive caregiver verbalization was infrequent and did not differ by type of food. Higher odds of accepting a bite were associated with the bite containing LNS, odds ratio (OR) 3.05; 90% confidence interval (CI) (1.98, 4.71), the child self‐feeding, OR 5.70; 90% CI (2.77, 11.69), and positive caregiver verbalization, OR 2.46; 90% CI (1.26, 4.80), while lower odds of acceptance were associated with negative child verbalization during feeding, OR 0.27; 90% CI (0.17, 0.42). In this sample, caregivers used more responsive feeding practices during bites of local complementary food and were more controlling when feeding LNS. Responsive caregiver behaviours predicted child acceptance of food. These results could be used to design interventions in Malawi to improve responsive feeding practices in general and during LNS use.